2020
DOI: 10.1523/eneuro.0081-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2-Like Receptors Modulate Intrinsic Properties and Synaptic Transmission of Parvalbumin Interneurons in the Mouse Primary Motor Cortex

Abstract: Dopamine (DA) plays a crucial role in the control of motor and higher cognitive functions such as learning, working memory and decision making. The primary motor cortex (M1), which is essential for motor control and the acquisition of motor skills, receives dopaminergic inputs in its superficial and deep layers from the midbrain. However, the precise action of DA and DA receptor subtypes on the cortical microcircuits of M1 remains poorly understood. The aim of this work was to investigate in mice how DA, throu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 50 publications
4
26
1
Order By: Relevance
“…An acute application of DA did not affect the excitability of PTNs in both controls and in 6-OHDA mice. These results are consistent with recent findings that dopaminergic modulation of pyramidal neurons is mainly mediated indirectly by parvalbumin-expressing interneurons in M1 (Vitrac et al, 2014;Cousineau et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An acute application of DA did not affect the excitability of PTNs in both controls and in 6-OHDA mice. These results are consistent with recent findings that dopaminergic modulation of pyramidal neurons is mainly mediated indirectly by parvalbumin-expressing interneurons in M1 (Vitrac et al, 2014;Cousineau et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…An acute application of DA did not rescue altered intrinsic excitability of PTNs and had minimal effects to intrinsic properties of ITNs in 6-OHDA mice. This indicated that loss of dopaminergic neuromodulation does not play a major role in the intrinsic adaptations of M1 pyramidal neurons in parkinsonian state, which is consistent with recent findings that dopaminergic modulation of pyramidal neurons is mainly mediated indirectly by parvalbumin-expressing interneurons in M1 (Vitrac et al, 2014;Cousineau et al, 2020). Thus, we propose that circuitry mechanisms underlie cellular adaptions in M1 in parkinsonian state.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to D1-like receptor expression, D2-like receptor expression does not decrease with aging in human hippocampus ( Seaman et al, 2019 ) and rodent area CA3 ( Amenta et al, 2001 ). D2-like dopamine receptors are mainly expressed on interneurons in the cortex ( Cousineau et al, 2020 ) and hippocampus ( Andersson et al, 2012b ) D2-like receptors inhibit adenylate cyclase activity and although this could reduce excitability, D2-like receptor activation increases fast-spiking interneuron activity and GABAergic inhibition ( Tseng and O’Donnell, 2007 ; Tomasella et al, 2018 ), probably through a β-Arrestin2–dependent inhibition of Akt and activation of Gsk3β ( Urs et al, 2016 ). In Addition, D2-like receptors can activate receptor tyrosine kinase-ERK signaling ( Kim et al, 2006 ; Beaulieu et al, 2011 ), which is critical for dopamine-induced enhancement of γ oscillation in young rats ( Xie et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, D2R stimulation in the prefrontal cortex of monkeys engaged in a cognitive task increases working memory encoding at both single neuron and population levels (Ott and Nieder, 2017 ). The resting and active properties of PV+ GABAergic interneurons are targets of D2R modulation (Cousineau et al, 2020 ). Moreover, a schizophrenia-related genetic deletion reduces the ability of D2Rs to gate the inhibition of excitatory neurons through PV+ inhibitory neurons in the cerebral cortex (Choi et al, 2018 ), providing a neural mechanism linking D2R-mediated function specifically in GABAergic interneurons to the pathophysiology of psychosis.…”
Section: Discussionmentioning
confidence: 99%